Permanent pacing across a tricuspid bioprosthesis - Krishnamoorthy, Jaishankar; Palkar, Ranjeet; Maharajan, Rashmi; Kalidoss, Latchumanadhas; Sethuratnam, Rajan; Ajit, Mullasari (SA Heart Journal, 2017)
Image in cardiology.